By definitions of the (co)tangent and cosecant function,
![3\tan^2x-2=\csc^2x-\cot^2x\iff3(\sin^2x)/(\cos^2x)-2=\frac1{\sin^2x}-(\cos^2x)/(\sin^2x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nrm29phe859jkqaui4eyqrfk832puqj00m.png)
Turn everything into fractions with common denominators:
![(3\sin^2x-2\cos^2x)/(\cos^2x)=(1-\cos^2x)/(\sin^2x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jnhpys1w8xxwhrp4qx8bo3p9qs6ap8yiiz.png)
Recall that
, so we can simplify both sides a bit.
On the left:
![(3\sin^2x+3\cos^2x-5\cos^2x)/(\cos^2x)=(3-5\cos^2x)/(\cos^2x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/a2a416ocmxwap91fp99n1pshvp8vnh402u.png)
On the right:
![(1-\cos^2x)/(\sin^2x)=(\sin^2x)/(\sin^2x)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6hedry08u1lfgaprgnamd2erz7nq0z7sa0.png)
(as long as
, which happens in the interval
when
or
)
So we have
![(3-5\cos^2x)/(\cos^2x)=1\implies3-5\cos^2x=\cos^2x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7pyg0mhzr33zixky9l91fya4epatx0iirm.png)
![\implies3=6\cos^2x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pxyufex71ahr4m1l9iad9d3wij7mz9ickn.png)
![\implies\cos^2x=\frac12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nzwlxdhlf5r0dtcdaoohhc1yjl18sbyo3b.png)
![\implies\cos x=\pm\frac1{\sqrt2}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/os1zai1v7vgqj6tovjh5tz39f12nunsnyh.png)
![\implies x=\frac\pi4\text{ or }x=\frac{3\pi}4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3f7s6tp7jk035jcylkzm9ko5u6pt964ise.png)